Intestinal bacteria are involved in Radix Glycyrrhizae and Radix Euphorbiae Pekinensis incompatibility. (12th June 2021) - Liu, Siqi; Qiao, Shanshan; Wang, Sha; Tao, Zhi; Wang, Jing; Tao, Jiayue; Wang, Qiaoxia; Gu, Xuan; Chen, Meng; Wang, Rufeng
Abstract: Ethnopharmacological relevance: Eighteen Incompatible Medicaments (EIM) belongs to the category of incompatibility of Traditional Chinese medicine (TCM). This theory forbids concomitant using any one of the eighteen herbal pairs such as Radix Glycyrrhizae (RG)-Radix Euphorbiae Pekinensis (REP), Radix Aconiti-Bulbus Fritiliariae Cirrhosae, and Radix et Rhizoma Veratri Nigri-Radix Ginseng. Concomitant using RG and REP could result in more serious adverse effects on major organs such as kidney, heart, and liver. Aim of the study: To investigate the effects of RG-REP decoctions on gut microbiota and short-chain fatty acids (SCFAs) for the purpose of elucidating the mechanism of RG-REP incompatibility. Materials and methods: Six groups of male SD rats were intragastrically administrated with distilled water, RG decoction, REP decoction, 1:1 RG-REP decoction, 2:1 RG-REP decoction and 3:1 RG-REP decoction, respectively, twice daily for 30 consecutive days, and the feces of each rat was separately sampled for gut microbiota analysis and SCFAs assay. 16S rDNA sequencing was employed to comparatively investigate the structure and abundance of intestinal bacteria in rat feces. Gas chromatography (GC) was used to quantitatively determine the contents of SCFAs in rat feces and in vitro samples. The correlation between bacteria and the production of SCFAs was analyzed by Spearman correlation analysis. An in vitro model of human intestinal bacteria was also constructed to simulate and validate the in vivo experiment. Results: The contents of butyric acid in both rat feces and in vitro samples decreased in RG-REP groups. The general structure of gut microbiota in RG-REP groups was not significantly different from that in control group. However, RG alone increased the abundance of Lactobacillus while this effect was counteracted by concomitant using with REP. REP alone decreased the abundance of two interrelated species, Akkermansia and Butyricimonas, and this effect was strengthened by concomitant using REP with RG in the ratio of 1:1. In comparison with REP alone, RG-REP combination also significantly increased the abundance of Streptococcus and Prevotella . Conclusion: The incompatibility of RG-REP combination is associated with its negative effect against probiotic bacteria and positive effect on conditional pathogenic bacteria as well as its inhibition on butyric acid production. Graphical abstract: Image 1 Highlights: This is the first report that intestinal bacteria are involved in RG-REP incompatibility. The influence of RG-REP combinations on microbiota was evaluated by both in vivo and in vitro experiments. RG-REP incompatibility is associated with its disturbance on microbial composition and butyric acid production.